IMPLEMENTASI NETWORK DAN SERVER MONITORING MENGGUNAKAN ZABBIX BERBASIS LINUX INTEGRASI REALTIME NOTIFIKASI TELEGRAM DI PT. ARSEN KUSUMA INDONESIA - BADYA PRISAI NUGRAHA; Niki Ratama (CV. Multi Kreasi Media, 2022)
Internet Service Provider (ISP) is a company that provides internet services. A network monitoring system is a very crucial need for technology companies such as Internet Service Providers, because customers will greatly prevent when there is interference with the Internet Service Provider network they are using. Therefore, this research creates a Network Monitoring System that can send notifications in real time in order to make it easier for the technical team to find out information about disturbances directly so that they can speed up the technical team in solving problems and can find out the point of disturbances that occur so that the impact of the disturbance does not last long. . As a result, we use Zabbix which is integrated with Telegram to make it easier for the Arsen technical team to find out information and find out the trouble points that occur in real time so that the Arsen technical team can quickly troubleshoot problems that occur.